Ammonium Nitrate Blasting Agents from Manufacture to Field Use - Fred C. Drury (International Society of Explosives Engineers, 1980)
The introduction and growth of modern chemical explosives based upon prilled ammonium nitrate has been the most significant development in the explosives industry during the 20th century. These modern chemical explosives have been of incalculable value to our society. Their use has permitted a reduction of blasting costs, improved safety, and the development of new resource sources which would not have been accessible without this new technology.